Transition metal nanoparticles stabilized by ammonium salts of hyperbranched polystyrene: effect of metals on catalysis of the biphasic hydrogenation of alkenes and arenes. Issue 37 (16th September 2015) - Gao, Lei; Kojima, Keisuke; Nagashima, Hideo
Abstract: Hyperbranched polystyrene bearing ammonium salts (HPS-NR3 + Cl − ) behaves as an excellent stabilizer of ruthenium, rhodium, iridium, palladium, and platinum nanoparticles from 1 to 3 nm in size uniformly dispersed in the polymer matrix. The catalytic performance of the resulting metal-polymer composites, M@HPS-NR3 + Cl −, is dependent on the metal. This dependence was investigated by assessing the hydrogenation of alkenes and arenes. The utility of M@HPS-NR3 + Cl − as reusable catalysts in aqueous/organic biphasic systems was demonstrated by examining the catalysis of the hydrogenation of aromatic compounds containing various functional groups by Ru@HPS-NR3 + Cl − . Graphical abstract: